Detection of the presence of coliform in Syrian shenglish cheese (Damascus University Journal of agriculture sciences, 2021)
Abstract:  The purpose of this research was to evaluate shenglish cheese in Syrian by determining some chemical and microbial properties for /100/ samples collected randomly from different Syrian cities and urban markets during two year periods.The results showed that all samples were rejected by Syrian Normal Standard for fat and sodium chloride. And all samples were compatible for dry matter and moisture content. On the other hand, the percent of health rejection was very high reached to 100% of samples. The total count of coliform was more than 104 CFU. Bacteria includes the genus: Escherichia,  Aeromonas  and Vibrio .
Keywords: shenglish; coliform; chemical; microbial; API